2021
DOI: 10.1016/j.cardfail.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation Provides Multiyear Improvements in Autonomic Function and Cardiac Electrical Stability in the ANTHEM-HF Study

Abstract: Background: Patients with heart failure with reduced left ventricular ejection fraction (LVEF) (HFrEF) experience long-term deterioration of autonomic function and cardiac electrical stability linked to increased mortality risk. The Autonomic Neural Regulation Therapy to Enhance Myocardial Function in Heart Failure (ANTHEM-HF) trial reported improved heart rate variability (HRV) and heart rate turbulence (HRT) and reduced T-wave alternans (TWA) after 12 months of vagus nerve stimulation (VNS). We investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…In the present study, LLVNS significantly prevented the incidence of VAs, which was consistent with published findings of VNS during myocardial ischemia in animal models (6)(7)(8)(9)21). Lately, Nearing et al found VNS provided cardiac electrical stability and significantly prevented non-sustained VT in the ANTHEM-HF study (14). In contrast to previous studies, the dose of LLVNS without HR changes in this study could reach the therapeutic target zone reported by previous studies and contributed to satisfactory autonomic engagement for cardiac control (18,22).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, LLVNS significantly prevented the incidence of VAs, which was consistent with published findings of VNS during myocardial ischemia in animal models (6)(7)(8)(9)21). Lately, Nearing et al found VNS provided cardiac electrical stability and significantly prevented non-sustained VT in the ANTHEM-HF study (14). In contrast to previous studies, the dose of LLVNS without HR changes in this study could reach the therapeutic target zone reported by previous studies and contributed to satisfactory autonomic engagement for cardiac control (18,22).…”
Section: Discussionsupporting
confidence: 92%
“…However, two large clinical trials failed to demonstrate that VNS could improve cardiac function or reduce mortality (10,11). Another study showed VNS was a promising therapy in heart failure (HF) (12)(13)(14)(15)(16). The interfaces and stimulation protocols used among the abovementioned studies were various, probably contributing to different results (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…VNS has been applied as a therapy for patients with heart failure (24). However, large clinical studies on VNS have had mixed results (10)(11)(12)(13)(14)(15)(16). A posthoc analysis showed that various neural targets, VNS doses and HR responses may explain the reasons for different results (17).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological and device‐based interventions that enhance parasympathetic tone should be considered. Vagus nerve stimulation, while reducing seizure frequency, 92 protects the heart through multiple antiadrenergic, 93 antiapoptotic, 94 and anti‐inflammatory actions, 94 and through reduction in cardiac electrical instability 7,52,53,95 …”
Section: Diagnostic and Therapeutic Implications Of “Epileptic Heart Syndrome” Statusmentioning
confidence: 99%